Context-dependent costs and benefits of a heterospecific nesting association. (5th April 2018) - Swift, Rose J; Rodewald, Amanda D; Senner, Nathan R
Abstract : The costs and benefits of interspecific interactions can vary among spatial or temporal contexts. We studied interactions between breeding shorebirds and gulls and found that the nature of interactions varied with breeding stage. Hudsonian Godwits aggregated their nests near colonies of Mew Gulls, a protector species that reduced risk of predation that godwits experienced during incubation. However, the association changed post-hatching, when Mew Gulls became important predators of young chicks and were avoided by godwits. Abstract: The costs and benefits of interactions among species can vary spatially or temporally, making them context-dependent. For example, benefits associated with nesting near species that deter predators may give way to costs if the association increases the risk of predation during other stages of reproduction. We examined the extent to which the costs and benefits of heterospecific aggregations between a declining shorebird, the Hudsonian Godwit ( Limosa haemastica ), and a potential protector and predator, the Mew Gull ( Larus canus ), varied with breeding stage. Specifically, we assessed the spatial distribution and fate of 43 godwit and 262 gull nests in Beluga, Alaska, from 2014 to 2016. We then evaluated the effect of habitat and proximity to gulls on daily survival rates of 120 godwit nests from 2009 to 2016. We also examined the relationship between the proximity to gulls and survival of godwit chicks to 5 days old, the period when they are vulnerable to gull predation. Nests of godwits and gulls were significantly clustered across the landscape, a pattern that habitat heterogeneity failed to explain. Hatching success of godwit nests improved with proximity to the gull colony and increasing numbers of gull nests within 200 m. In contrast, survival of godwit chicks to 5 days improved with increasing distance to the gull colony. The costs and benefits that godwits derived from associating with Mew Gulls were thus context-dependent, with benefits pre-hatch and costs post-hatch. Our results show how spatiotemporal variation in species interactions precludes simple generalizations about the nature of their outcomes.